The First Female Dry Immersion (NAIAD-2020): Design and Specifics of a 3-Day Study - Tomilovskaya, Elena; Amirova, Liubov; Nosikova, Inna; Rukavishnikov, Ilya; Chernogorov, Roman; Lebedeva, Svetlana; Saveko, Alina; Ermakov, Ivan; Ponomarev, Ivan; Zelenskaya, Inna; Shigueva, Tatiana; Shishkin, Nikita; et al. (Frontiers in Physiology, 2021)
The article describes the procedure and some results of the first study on the female Dry Immersion. The results of the studies did not find significant risks to women's health and showed the feasibility of using this model of the effects of space flight with the participation of women of reproductive age.